What Really Matters In Operations Management Learning and Teaching - Bothams, John F. (Proceedings of the International Conference on Networked Learning, 2002)
This paper discusses the issues around the design and delivery of an Operations Management module in an MSc. in Business Information Technology. The course was designed to illustrate experientially what really matters for Operations Managers in the 21st century. It involved 70% of the content being presented face to face by groups of students and this learning aided through the use of electronic means including the use of the internet, intranet, electronic mind-mapping and on-line student created shared resources. The course and its objectives are described together with a description of how it was run. In normal academic results (marks) terms this process can be seen to be successful. Student reaction collected over the two runs in two years of delivery is described and illustrated. Some generalized implications are presented, but key is a holistic design of learning and assessment, with active learning which provides psychological safety and opportunities for personal development as well as content understanding.